2023
DOI: 10.1021/jacsau.2c00673
|View full text |Cite
|
Sign up to set email alerts
|

Near Quantitative Removal of Selenate and Sulfate Anions from Wastewaters by Cocrystallization with Chelating Hydrogen-Bonding Guanidinium Ligands

Abstract: Selenium (Se) has become an environmental contaminant of aquatic ecosystems as a result of human activities, particularly mining, fossil fuel combustion, and agricultural activities. By leveraging the high sulfate concentrations relative to Se oxyanions (i.e., SeO n 2– , n = 3, 4) present in some wastewaters, we have developed an efficient approach to Se-oxyanion removal by cocrystallization with bisiminoguanidinium (BIG) ligands that form crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We infer that the poor solubility of the triptycene backbone in methanol, together with the high polarity of methanol, drive the formation of 1, consistent with the multiple noncovalent interactions between building blocks that are observed in the structure (see above). 20 The same framework could be prepared using the parent 2-formylpyridine C instead of B, which generated a structure designated 1 H instead of 1 F , but the fluorine atoms of 1 F aided in its characterization, as noted below.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We infer that the poor solubility of the triptycene backbone in methanol, together with the high polarity of methanol, drive the formation of 1, consistent with the multiple noncovalent interactions between building blocks that are observed in the structure (see above). 20 The same framework could be prepared using the parent 2-formylpyridine C instead of B, which generated a structure designated 1 H instead of 1 F , but the fluorine atoms of 1 F aided in its characterization, as noted below.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 1 Dicationic sulfate precipitants reported by Custelcean's group [23][24][25] and our group. 26…”
Section: Introductionmentioning
confidence: 85%
“…[23][24][25] Very recently, Einkauf and Custelcean reported that these BIG 2+ precipitants could also precipitate selenate and selenite anions: while no selectivity was observed between the very similar sulfate and selenate anions, > 99% of sulfate and/or selenate could be removed by using an excess of precipitant. 25 Inspired by Custelcean's work, we recently reported that the simple bis-amidinium compound 1 2+ could remove > 95% of sulfate from aqueous solution and was selective for this anion even in the presence of competitive divalent anions. 26 Like Custelcean's precipitants, 23-25 1 2+ could be regenerated for subsequent reuse.…”
Section: Introductionmentioning
confidence: 99%
“…Cr(VI) anions are known to strongly interact with guanidinium cations through a combination of ionic and hydrogen bonding [41][42][43][44][45][46][47][48][49][50][51][52]. Theoretical studies have indeed demonstrated that the hydrogen bond interactions between the bidentate guanidinium and oxyanion-charged species produce very strongly bound complexes [48].…”
Section: Rationalementioning
confidence: 99%
“…Furthermore, the guanidine moiety of arginine is responsible for the strong arginine-phosphate interactions of proteins [42]. Thanks to its peculiar molecular geometry, charge distribution, and hydrogen bonding ability, the guanidinium ion can indeed strongly bind bidentate oxyanions, including, inter alia, carboxylate, phosphate, sulfate, nitrate, and selenate [43][44][45][46][47][48][49]. Unsurprisingly, it has been reported that polyhexamethylene-guanidine modified natural zeolitic materials [50], and guanidinium-based ionic organic covalent nanosheets [51,52] uptake considerable amounts of Cr(VI) oxyanions from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%